Content analysis of science books, based on Montessori educational model (ninth grade case of the first high school) - Seyed rasool Toudar (Institute of Management fekrenoandish, 2021)
The aim of this study was to analyze the content of the ninth grade science textbook of the first year of high school based on the Montessori educational model. The method of the present study was descriptive content analysis. The statistical population of this study was the textbooks of the first year of high school in the academic year 2018-2019, which were compiled and published by the textbook planning and writing office. The ninth grade science textbook of the first year of high school was selected by means of purposeful sampling method, and all its chapters were examined according to the components of the Montessori educational model. The used instrument was a researcher-made checklist of components of the Montessori educational model. The tables related to the components of the Montessori educational model were presented by means of the descriptive statistics. The findings of this study showed that; in the content of the ninth grade science textbook of the first year of high school, the component of learning environment has received the most attention, while the component of content and organization has received the least. The findings of this study can help planning to provide appropriate content and organizing in experimental science textbooks.